Advancing Molecular Therapies through In Vivo Bioluminescent Imaging - Anton McCaffrey; Mark A. Kay; Christopher H. Contag (Molecular Imaging)
Effective development of therapeutics that target the molecular basis of disease is dependent on testing new therapeutic moieties and delivery strategies in animal models of human disease. Accelerating the analyses of these models and improving their predictive value through whole animal imaging methods, which provide data in real time and are sensitive to the subtle changes, are crucial for rapid advancement of these approaches. Modalities based on optics are rapid, sensitive, and accessible methods for in vivo analyses with relatively low instrumentation costs. In vivo bioluminescent imaging (BLI) is one of these optically based imaging methods that enable rapid in vivo analyses of a variety of cellular and molecular events with extreme sensitivity. BLI is based on the use of light-emitting enzymes as internal biological light sources that can be detected externally as biological indicators. BLI has been used to test spatio-temporal expression patterns of both target and therapeutic genes in living laboratory animals where the contextual influences of whole biological systems are preserved. BLI has also been used to analyze gene delivery, immune cell therapies, and the in vivo efficacy of inhibitory RNAs. New tools for BLI are being developed that will offer greater flexibility in detection and analyses. BLI can be used to accelerate the evaluation of experimental therapeutic strategies and whole body imaging offers the opportunity of revealing the effects of novel approaches on key steps in disease processes.